A study of cultural elements in high level Chinese language textbooks for primary national school / Lim Kian Ming and Fan Pik Shy - Ming, Lim Kian; Shy, Fan Pik (Universiti Teknologi MARA, 2021)
goal of Teaching Chinese as a Second Language (TCSL) is to cultivate communication competence among students through their respective target languages. To achieve this, there is a correlation between the cultural elements and language teaching for the higher level studies of second language study. Textbooks play a crucial role as a medium to disseminate the cultural elements of TCSL. Extensive analysis of the cultural elements in the National Primary School's Chinese Language (BCSK) textbooks, cross-cultural awareness of TCSL and cultural compatibility is vital to cultivate communicative competence among students and prevent misunderstanding and conflicts. This study examines the cultural elements in Teaching Chinese as a Second Language (TCSL) based on six high-level of National Primary School's Chinese Language (BCSK) textbooks, which are textbooks of BCSK KBSR (Primary School Integrated Curriculum) Standard four to Standard six and textbooks of BCSK KSSR (Primary School Standard Curriculum) Standard four to Standard six in order to investigate the changes of cultural elements content and describe the features of cultural elements in this two sets of high-level BCSK textbooks. Researcher has used library research methods and information technology methods to collect data and then use quantitative and qualitative analysis methods to calculate cultural elements in high-level BCSK textbooks by referenced to the criteria of classification of cultural elements which designed by researcher based on previous studies as well as the references of TCSL experts. The results showed that (1) high level BCSK KSSR textbooks are found that had more cultural elements for the total number of 622 compared to 522 in high-level BCSK KBSR textbook with the increasing of 19.16% and (2) high-level BCSK KSSR textbooks can be said to be more ideal to fostering communicative competence as the cultural elements in this set of BCSK textbooks are more geared towards communicative cultural elements with a record rate of 46.30% compared to 39.27% only in high-level BCSK KBSR textbooks. The outcome of this research will aid/help the writer and the BCSK textbook editor to integrate the language and communicative culture to reach a high degree of perfection and serve as a guideline/basis for readiness, analysis, and TCSL development in the future. TCSL preparation and strategy needs to be proven by the classroom practices and language teaching in BCSK classes. The cultural elements also need to be inclusive; by involving non-linguistic cultural elements such as sign language, body language, et cetera in communication which happen in real life. Thus, in-depth research for textbook as relevant TCSL teaching material will be further explored in the future.